II Workshop on Modeling and Simulation for Science and Engineering (2020)
II Workshop on Modeling and Simulation for Science and Engineering (II WMSSE) was a conference conducted at Universidad Tecnológica de Bolívar, in the city of Cartagena de Indias, Colombia, on September 24, 25 and 26, 2019. There, works in several topics of science, technology and engineering were presented. Specially, the participants of conference wanted to bring some solutions to the actual industrial requirements such as improvement and optimization of the heat transfer equipment, electronic devices, system control by mean of computational modeling. Also, dynamic system control was widely used for the prediction of power flow market, diffusion of bacteria in coffee production, stress concentration in industrial machines, analysis of population dynamics, model of hydrological and pluviometric networks, encryption for intercommunication of substation control centers, and others.